Civilisation as a Sign: new perspectives in civilisation studies - Oukhvanova-Shmygova, Irina F.; Ryushyna, Lilia L. (Respectus Philologicus, 2006)
The problem of the future of the Eastern and Western civilizations has come to the fore in  civilization studies. There are researchers who insist on the idea of their cooperation, which represents itself whether in a dialogue form (polilogue) or in the form of absorbing one civilization by another. There are also researchers who believe that civilizations do not have much in common, and which is why conflicts are unavoidable. As a result, there appeared four models of civilization development, namely: the Europe-centrism model, the model of the parallel development of the West and East, the model of the clash of civilizations and the model of cultural dialogue. Could they be viewed as something holistic but open to different realizations? The authors give the idea of a synthetic (or rather synergetic) approach to treating civilization development built with the help of the causal-genetic perspective.
Keywords: sign; causal-genetic perspective; idea-biased content of civilization; phenomenonbiased content of civilization; civilisation